Baseline levels of seminal reactive oxygen species predict improvements in sperm function following antioxidant therapy in men with infertility. (12th October 2020) - Vessey, Wayne; Saifi, Shaghayegh; Sharma, Aditi; McDonald, Cassandra; Almeida, Paula; Figueiredo, Monica; Minhas, Suks; Virmani, Ashraf; Dhillo, Waljit S.; Ramsay, Jonathan W.; Jayasena, Channa N.
Abstract: Background: Poor sperm function is a major cause of infertility. There is no drug therapy to improve sperm function. Semen oxidative stress is a recently identified pathway for sperm damage. Commercial antioxidants such as L‐carnitine and acetyl‐L‐carnitine (LAL) are commonly self‐administered by infertile men. However, concerns have been raised whether inappropriate LAL therapy causes reductive stress‐mediated sperm damage. It is imperative to investigate whether: (1) LAL improves sperm function by reducing reactive oxidative species (ROS); (2) LAL has differential effects on sperm function between men with normal and elevated ROS. Methods: A prospective cohort study of routine clinical practice was performed in infertile men with abnormal sperm quality. Changes in sperm function and semen ROS levels following three months of oral LAL therapy were compared between participants with baseline seminal normal ROS (≤10RLU/SEC/10 6 sperm; n = 29) and High ROS (>10 RLU/SEC/10 6 sperm; n = 15) levels measured using an established colorimetric‐luminol method. Results: In normal ROS group, sperm function did not change following LAL therapy. In high ROS group, LAL therapy reduced semen ROS fivefold, increased sperm count by 50% (mean count in mill/ml: 21.5 + 7.2, baseline; 32.6 + 9.5, post‐treatment, P = .0005), and total and progressive sperm motility each by 30% (mean total sperm motility in % 29.8 + 5.0, baseline: 39.4 + 6.2, post‐treatment, P = .004; mean progressive sperm motility in % 23.1 + 4.6, baseline: 30.0 + 5.5, post‐treatment, P = .014 vs. baseline). Conclusions: We report for the first time that LAL only improves sperm quality in infertile men who have baseline high‐ROS levels prior to treatment. These data have important potential implications for couples with male infertility and their clinicians.